2003
DOI: 10.1002/jsfa.1589
|View full text |Cite
|
Sign up to set email alerts
|

Blanching and long‐term freezing affect various bioactive compounds of vegetables in different ways

Abstract: An extensive study on the effects of blanching/freezing and long-term freezer storage on various bioactive compounds of more than 20 commonly used vegetables was performed. Effects were strongly plant species-dependent. Contents of dietary fibre components either were not affected or increased slightly. Minerals in general were also stable, but some losses of soluble minerals by leaching were observed. Phenolic antioxidants and vitamins were clearly more sensitive. Significant losses (20-30%) of antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
122
3
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(150 citation statements)
references
References 57 publications
17
122
3
5
Order By: Relevance
“…There was a higher reduction in DPPH RSC up to 6 min, in comparison to the lower temperature range, after which the DPPH RSC remained almost constant. Puupponen-Pimiä et al (2003) measured the AO capacity by the DPPH assay in blanched cauliflower and reported a reduction of 20-30%, which is less than that reported in the present study.…”
Section: Changes In Dpph Radical Scavenging Capacitycontrasting
confidence: 91%
“…There was a higher reduction in DPPH RSC up to 6 min, in comparison to the lower temperature range, after which the DPPH RSC remained almost constant. Puupponen-Pimiä et al (2003) measured the AO capacity by the DPPH assay in blanched cauliflower and reported a reduction of 20-30%, which is less than that reported in the present study.…”
Section: Changes In Dpph Radical Scavenging Capacitycontrasting
confidence: 91%
“…In the last few decades, attention on naturally occurring antioxidants in foods has increased because of the adverse effect of synthetic antioxidants and the practice of minimum usage of artificial food additives. Nutritional value or texture of food could be affected or lost during the heat treatments or storage as most of the bioactive compounds and naturally occurring antioxidants are susceptible to heat (Amin and Lee 2005;Puupponen-Pimia et al 2003;Pokorny and Schmidt 2001). Recent studies showed that appropriate cooking methods for different vegetables may maintain the antioxidant properties or improve their nutritional value (Galor et al 2008;Ng et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The recorded decrease of AA level in peas after 10 months of storage (about 26.8%) was not very significant and it was the lowest among all analysed crops. Puupponen-Pimia et al (2003) observed a higher decrease (41.7-55.6%) of AA in peas during 12 months freezing.…”
Section: Resultsmentioning
confidence: 75%